PTPRO represses breast cancer lung metastasis by inhibiting the JAK2-YAP axis - Xiao Xiong; Jingfang Liu; Xiaotong Wu; Zhimeng Yao; Yuhua Meng; Shuang Liu; Yexi Chen; Hongzheng Ren; Shegan Gao; Xiaofu Qiu; Hao Zhang (Scientific Reports)
Abstract Lung metastasis is the primary cause of breast cancer-related mortality. Protein tyrosine phosphatases such as PTPRO are important in cancer progression. However, the role and underlying mechanisms of PTPRO in breast cancer lung metastasis are largely unknown. The function of PTPRO in breast cancer metastasis was examined in mice with ptpro deficiency driven by the PyMT promoter. The regulatory role of PTPRO in JAK2–YAP activation was tested in cell-based knockdown, overexpression and catalytic-dead mutation assays. Bioinformatics analyses and assays of human cancer specimens and mouse tumour samples were performed to investigate PTPRO-regulated pathways and functions. Ptpro deletion in MMTV-PyMT transgenic mice led to increased lung metastasis. Bioinformatics analyses and subsequent assays of human breast cancer specimens revealed a reverse correlation between PTPRO expression and JAK2–YAP pathway activity. Both in vitro and in vivo data demonstrated that PTPRO inactivates the JAK2–YAP pathway and diminishes the metastatic ability of breast cancer. Analysis of catalytic-dead PTPRO mutant breast cancer cells confirmed that functional PTPRO is a determinant of the activation of the JAK2–YAP pathway and the suppression of breast cancer metastasis. Data from patient, animal and cell-based models collectively demonstrated that PTPRO suppresses breast cancer lung metastasis by inhibiting JAK2–YAP dephosphorylation. Therefore, strengthening PTPRO or targeting PTPRO-mediated pathways could be potential strategies for inhibiting breast cancer lung metastasis.